The Dose-Related Efficacy of Acupuncture on Endometrial Receptivity in Infertile Women: A Systematic Review and Meta-Analysis - Zheng, Xiaoyan; Yu, Siyi; Liu, Liying; Yang, Han; Wang, Fangge; Yang, Hongmei; Lv, Xingyu; Yang, Jie (Frontiers in Public Health, 2022)
Background Progress has been achieved by using acupuncture widely for poor endometrial receptivity (PER). However, different acupuncture dosages may lead to controversy over efficacy. Objective To evaluate the evidence-based conclusions of dose-related acupuncture on infertile women with PER. Method References were retrieved from nine databases from inception to 26 February 2022. This meta-analysis included randomized controlled trials (RCTs) that investigated the dose-related efficacy of acupuncture for PER with outcomes of endometrium receptivity (ER) parameters by transvaginal sonography (TVS) and the subsequent pregnancy outcomes in three acupuncture-dose groups: the high-dosage group (three menstrual cycles), the moderate-dosage group (one menstrual cycle), and the low-dosage group (two or four days). Since there remained sufficient heterogeneity among the three subsets, we prespecified seven subgroup variables (four clinical and three methodological) to investigate the heterogeneities. Results A total of 14 RCTs (1,564 women) of moderate or low overall quality were included. The results were different when the dosage of acupuncture was restricted. For the moderate or high-dosage group, CPR and part of ER parameters were improved in the acupuncture group (i.e., CPR: OR = 2.00, 95% CI [1.24, 3.22], p = 0.004, I2 = 0% in one menstrual cycle; OR = 2.49, 95%CI [1.67, 3.72], p < 0.05, I2 = 0% in three menstrual cycles). However, for the low-dosage group, no statistical difference was observed in CPR (OR = 0.07, 95% CI [−0.10, 0.23], p = 0.44, I2 = 82%) and a part of the ER parameters. In subgroup analysis, four subgroup variables (the routine treatment, risk of performance bias, duration of acupuncture treatment, and the age of participants) could explain some of the heterogeneities across all trials. Conclusion The finding indicated that the trend of relatively more acupuncture dosage showed better effects for poor endometrial receptivity among PER women. It remains a potential heterogeneity in our studies. Further high-quality trials with a homogeneity trial design need to be conducted.